Investigation Study of Additional Water's Effect on Ash-Based Geopolymer Concrete - Fitrahaldi, Naufal; Herwani, Herwani; Faisal, Faisal (Fakultas Teknik Universitas Tanjungpura, 2025)
Geopolymer concrete is a form of concrete where the traditional Portland cement binder is substituted with alternative materials rich in silica and aluminum. Cement production involves a high-temperature combustion process, reaching 1.500 °C, which produces large amounts of carbon dioxide (COâ‚‚) emissions, roughly equivalent to the amount of cement produced. Due to the significant environmental impact of traditional cement production, there has been a growing emphasis on developing geopolymer concrete that uses fly ash as an alternative binder in concrete mixtures. This study adopts an experimental approach to fabricate geopolymer concrete specimens incorporating fly ash. The study involves testing to assess both the physical and mechanical properties. The findings indicated a slump range of 16-28 cm, an average density ranging from 2.274,501 Kg/m ³ to 2.322,177 Kg/m ³, a 28-day compressive strength between 11,247 MPa and 15,915 MPa, split tensile strength varying from 1,179 MPa to 1,721 MPa, and elasticity modulus between 2.003,573 MPa and 3.417,811 MPa. The optimal variation was achieved by adding 0% water. Thus, geopolymer concrete incorporating fly ash holds considerable promise as an environmentally sustainable substitute for traditional cement-based binders.